LIGHTWEIGHT AUTONOMOUS SYSTEM EVALUATION PLATFORM - BENTLEY, PETER VAN TUYL; BRADLEY, MATTHEW THOMAS; BECKER, BRIAN C; LE BORGNE, MARIO; WOJTASZEK, TIMOTHY PATRICK; FALK, NATHAN; HARRIS, JACK WYATT (2024)
An example method includes (a) generating a request to obtain log data descriptive of operation of an autonomous vehicle control system in a subject scenario, the log data indexed by an indexing parameter; (b) submitting the request to a log repository service, the log repository service configured to receive the request and serve, responsive to the request, log metadata; (c) loading, based on the log metadata and an index value of the indexing parameter, a log data sketch associated with the index value; and (d) loading, based on the log metadata and the index value, and responsive to an inspection indicator, detailed log data associated with the index value.